Profiling the Interrogee: Applying the Person-Centered Approach in Investigative Interviewing Research - Palena, Nicola; Caso, Letizia; Cavagnis, Lucrezia; Greco, Andrea (Frontiers in Psychology, 2021)
In the past, deception detection research has explored whether there were specific personal characteristics that were related to lying and found that factors such as personality and morality are indeed related to lying. However, past research has usually focused on a variable-centred approach. Yet, a person-centred might be more suitable here as it allows for the study of people in an integrative manner. In this experiment, 673 students completed a questionnaire which included measures of the five factors of personality, the level of moral disengagement, the perceived cognitive load when lying, lying strategies, frequency of lying and the LiES scale, a tool measuring the tendency to tell self-oriented, altruistic and vindicative lies. We performed a Latent Profile Analysis to integrate personality, moral disengagement, and perceived cognitive load scores into specific profiles. Then, we related profile membership to lying behaviour. We obtained four profiles, and found that extraversion, moral disengagement and the perceived cognitive load contributed most to profile differences. We also found that lying frequency did not differ across profiles, whereas lying tendency did. In conclusion, our results suggest that several facets of the individual play a role in lying behaviour, and that adopting a person-centred approach might be a good strategy to explore the role of interpersonal differences in lie detection research.